The extent to which employees are released from work for examiner tasks - Wenzelmann, Felix [Verfasser]; Risius, Paula [Verfasser] (My University, 2020)
"Intermediate and final examinations represent a major commitment for candidates, but examination board members must also devote considerable time to conducting them. This means that firms then need to release staff from their normal tasks. This article highlights the extent to which this happens and provides a breakdown of the firms making the greatest contribution in this regard. It also includes an estimate of costs incurred." (authors' abstract; BIBB-Doku)
Keywords: L 7 Prüfungen; Prüfung; Prüfer; Prüfungsausschuss; Betrieb; Freistellung; Kosten